2021
DOI: 10.1155/2021/6652858
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Hepatic Encephalopathy and Biejia-Ruangan Are Associated with First Hospital Readmission in Nonalcoholic Cirrhosis Patients

Abstract: Introductionand Aim. Patients with cirrhosis are often hospitalized repeatedly for a variety of complications. This retrospective study aimed to assess the effects of minimal hepatic encephalopathy (MHE) and Biejia-Ruangan (BR) on first hospital readmission in nonalcoholic cirrhosis patients without previous overt hepatic encephalopathy (OHE) or hepatocellular carcinoma (HCC). Materials and Methods. A total of 176 hospitalized patients with nonalcoholic cirrhosis were included in this retrospective study. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Several studies have confirmed that FZHY can significantly improve liver function and ameliorate TCM symptoms caused by liver dysfunction by reducing collagen synthesis, promoting extracellular matrix degradation, and reversing liver fibrosis [6][7][8] . We recently demonstrated that the use of Biejia Ruangan could decrease the risk of hospital readmission in cirrhotic patients with minimal HE (MHE) [9] . In addition, our prior study found that the administration of FZHY exerted a protective effect against hepatocellular carcinoma in patients with HBC [10] .…”
mentioning
confidence: 99%
“…Several studies have confirmed that FZHY can significantly improve liver function and ameliorate TCM symptoms caused by liver dysfunction by reducing collagen synthesis, promoting extracellular matrix degradation, and reversing liver fibrosis [6][7][8] . We recently demonstrated that the use of Biejia Ruangan could decrease the risk of hospital readmission in cirrhotic patients with minimal HE (MHE) [9] . In addition, our prior study found that the administration of FZHY exerted a protective effect against hepatocellular carcinoma in patients with HBC [10] .…”
mentioning
confidence: 99%